SOSIALISASI PENGGUNAAN YOUTUBE YANG SEHAT DAN BAIK BAGI MURID SD DHARMA KARYA UT, TANGERANG SELATAN - Ayuningtyas, Fitria; Abdullah, Ahmad Zakki (Jurnal Pengabdian Masyarakat AbdiMas, 2019)
The background of this activity is the increasing use of the Internet among children. Not only it formed an opinion but shaping the culture at large. The term of Ã¢â‚¬Å“social mediaÃ¢â‚¬Â and "gadget" is becoming more popular, especially in the urban environment which is now a remarkable phenomenon. The use of social media and gadgets cannot be limited by age, even in children with early age. Lots of parents who work full time, this sometime has put aside the importance of monitoring or assisting their son / daughter when using the internet. ItÃ¢â‚¬â„¢s quite a dilemma, because the use gadgets took big part in modern social development. The Millennial, a generation formerly known as digital natives, the age group that is equated with "authenticity" or a native who had been born in the digital environment. The age group that can no longer be separated with the gadget. There must be understanding in the form of good guidance and supervision in order to create good progress. Youtube provided a lot of good video were uploaded both of individually and group. During watching youtube, the role of parent to monitor their children while watching is very important. To implanted as well as to grow awareness and understanding of the user within the age (teenage and children) that could use this instrument as well as possible.Keywords : Healthy internet, children,Ã‚Â  youtube.